The Effect of Project Based Learning Model on Students' Critical Thinking Abilities in the Science Subject of Grade V UPTD SDN 124385 Pematangsiantar - tobing, Maria rezeki lumban; Thesalonika , Emelda; Purba, Natalina (PT. Hafasy Dwi Nawasena, 2025)
This study aims to determine the influence of the Project Based Learning learning model on students' critical thinking skills in the Social Science class V subject at UPTD SDN 124385 Pematangsiantar. This type of research is an experimental research because it aims to examine the relationship between the application of the Project Based Learning (PjBL) learning model and the improvement of students' critical thinking skills. This research was carried out by researchers at UPTD SD Negeri 124385 Pematangsiantar. The sample in this study is all grade V students at the school which totals 21 people. Data collection techniques are a very crucial stage in a research, because the main purpose of research activities is to obtain relevant data. Based on the results of the research and discussion in the previous section, it can be concluded that the application of the Project Based Learning (PjBL) learning model has a significant influence on improving the critical thinking skills of grade V students at UPTD SDN 124385. This can be seen from the increase in the average score of students, namely from 55 in the pretest to 85.25 in the posttest. The results of the normality test showed that the pretest data had a significance value of 0.097 and the posttest of 0.100, both of which were greater than 0.05. This shows that the pretest and posttest data are distributed normally. The results of the hypothesis test showed that the t_hitung value of 12.643 was greater than the t_tabel of 1.729, which means that the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. The N-Gain IV test also showed an increase with a value of 0.49, which is included in the moderate category because it is in the range of 0.30 < N-Gain < 0.70. These findings indicate that the application of the Project Based Learning learning model has a significant influence on students' critical thinking skills in Social Science subjects class V UPTD State Elementary School 124385 Pematangsiantar in the 2024/2025 Academic Year